Critical discourse analysis and translation: a comparative study of discourse and ideology in translated versions of Ibsen’s A doll’s house - Wing-bo, Anna Tso; Lee, Scarlet (Nordlit, 2015)
Chinese readers have shown excessive interest in Ibsen’s A Doll’s House (1879) since progressive Chinese intellectuals such as Lu Xun (1881–1936) and Hu Shi (1891–1962) translated and introduced the play to China in the early twentieth century. However, until today, not many have noticed or mentioned issues that could arise from translation. While Chinese scholars vigorously study Ibsen and modern Chinese drama, few care to read the original play (in Dano-Norwegian) or the English translation, let alone comparing them with the Chinese version(s), which most Chinese readers actually read. In view of this, we look into three translations of A Doll’s House – namely Peter Watts’s English version, Pan Jiaxun’s Chinese version, and Cao Kaiyuan’s Taiwanese version. By using the critical discourse analysis (CDA) approach, we discover that the discourse and power struggle of Nora and Torvald in Watts’s and Pan’s versions differ in various interesting ways. In this article, we will use the conversation between Nora and Torvald in the last scene of Act III to demonstrate how omissions, additions and alterations brought about by translations can change the discourse and create different ideological effects on gender relations and identities (192 words).